Prediction of New Fungal Pathogen Effector-like Proteins and Their Molecular Interactions with Their Host - Rozano, Lina (Curtin University, 2022)
This research made use of all publicly available, experimentally-determined 3D structures of fungal effector proteins to develop, validate and test a range of biomolecular modelling approaches to predict the structure, function and interactions of effector proteins. New protein folds and likely biological functions were identified within effector families, and a protocol based on a rigid docking approach was developed to differentiate between two different MAX binding regions on plant HMA domain proteins.